PELATIHAN PEMBUATAN APLIKASI KALKULATOR SEDERHANA MENGGUNAKAN VB.NET PADA SMK TRITECH MEDAN - Indriani, Ulfah; Syahputri, Nita; Br Simanjuntak, Anggi Canita (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2024)
The purpose of community service activities is to implement the Tri Dharma of Higher Education and provide learning how to make a simple calculator application at SMK Tritech Medan. The introduction of computer applications to vocational students can be a point of view for students if they will continue on to college. The application that will be used to make this simple calculator is Visual Studio or also known as VB.NET. Microsoft Visual Basic .NET (VB.NET) is a tool for developing and building applications that run on the .NET Framework system, using the BASIC language. VB.NET applications can be used to create a variety of other desktop applications. Here, VB.NET is used to create a simple calculator application as an introduction to the use of the application to students before they can later use VB.NET for the purposes of making larger applications.